A prospective study demonstrating improved visualization when capsule endoscopy is performed after preparation with polyethylene glycol and ascorbic acid - Mascarenhas Saraiva, M (2021)
Capsule endoscopy is used increasingly to obtain images of the gastrointestinal tract, yet it still remains unclear what is the best preparation for this type of exploration. Thus, the aim of this study was to compare the results of capsule endoscopy explorations performed after a basic preparation with a clear liquid diet, reduced iron intake and fasting or following preparation with a PEG/ascorbate solution. The results obtained from a prospective intervention group that used a PEG/ascorbate solution to prepare for capsule endoscopy were compared with those from a retrospective group of patients who followed the more basic preparation. The quality of visualization was assessed with the Park score, assessing visualization of the mucosal surface and the cleanliness of the intestinal lumen. The capsule transit time in different segments of the gastrointestinal tract was also evaluated. A significant improvement in the quality of small intestine visualization was observed in individuals prepared with the PEG/ascorbate solution as opposed to the basic preparation. Indeed, there were significant differences in the two separate components that contribute to the overall visualization score, with better mucosa visualization and lumen content scores in the intervention group, reflecting improved performance. The presence of diabetes appears to affect the results of these explorations, at least when employing the PEG/ascorbate preparation. As such, preparation with a PEG/ascorbate solution improves the results of capsule endoscopy when compared to a basic preparation, without the inconvenience of the more stringent preparations used for colonoscopies.